Hemiaminals : a new chemotype for organocatalysis - Ramaotsoa, Valerie (Department of Chemistry, 2015)
Jorgensen and List introduced enantioselective α-amination of an aldehyde with an azodicarboxylate as the electrophile using L -proline enamine catalysis in 2002. Following borohydride reduction, the α-hydrazino alcohol was obtained in high yield (93-99%) and enantioselectivity (86-97%). Application of the enantioselective α-amination reaction to an acetal as a masked aldehyde was developed in our group recently, and in part I of this thesis results on extending this chemistry to the α-amination of N-protected hemiaminals from N-heterocycles are reported, in which it was found that the reaction only worked with the carbonyl group exo to the ring. In the case of the hemiaminal derived from N-Boc or N-CBz 2-pyrrolidinone an amination with proline catalyst in acetonitrile over 3 days gave α-aminated products in high ee (77-84%). N-N bond hydrogenolysis using Raney Nickel and hydrogen, followed by oxidation to the lactam afforded the N -protected α-amino lactam in high enantioselectivity (78% and 8 6 %). In part II the development of a mild reduction of the N-N bond of the α-hydrazino amination products of straight-chain aldehydes is reported. The corresponding oxazolidinone- hydrazides are reduced to their oxazolidinones via a modified E1cB elimination using ethyl bromomalonate and potassium carbonate in acetonitrile. The reactions gave high yields (76-96%) and ees (83-95%) with a good chemoselectivity profile.